Digitalization of Sharia Economy: Welcoming a New Era of Modern Economy - Moch. Khoirul Faizin; Wahyudin Rahman; Edy Setiawan (Oikonomia : Journal of Management Economics and Accounting, 2025)
various economic sectors, including the sharia economy. This article discusses the process of digitalization in the sharia economy and its implications in welcoming the new era of the modern economy. This study aims to identify how digital transformation can strengthen the sharia economic system through financial technology innovation (sharia fintech), halal-based digital platforms, and online integration of sharia payment systems. The method used in this study is a descriptive qualitative study through literature analysis and secondary data. The results of the study indicate that digitalization has the potential to expand sharia financial inclusion, increase service efficiency, and strengthen transparency and consumer trust in Islamic economic principles. However, challenges such as digital literacy, regulation, and compliance with sharia principles are still major obstacles. Therefore, synergy between regulators, industry players, and academics is needed to ensure that digitalization is in line with the maqashid sharia and is able to encourage sustainable sharia economic growth.